2023
DOI: 10.1186/s12974-023-02752-7
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes display ultrastructural alterations and heterogeneity in the hippocampus of aged APP-PS1 mice and human post-mortem brain samples

Abstract: The past decade has witnessed increasing evidence for a crucial role played by glial cells, notably astrocytes, in Alzheimer’s disease (AD). To provide novel insights into the roles of astrocytes in the pathophysiology of AD, we performed a quantitative ultrastructural characterization of their intracellular contents and parenchymal interactions in an aged mouse model of AD pathology, as aging is considered the main risk factor for developing AD. We compared 20-month-old APP-PS1 and age-matched C57BL/6J male m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 161 publications
0
7
0
Order By: Relevance
“…As previous research has identified DM (and intermediate microglia, presenting features of both typical microglia and DM) as an abundant cell population in aging and neurodegenerative disease pathology (3,39,45,46), a quantitative approach to measuring the shade, or “darkness”, of microglia on electron micrographs was next employed. Using ImageJ, the integrated density of microglial cytoplasm and integrated density of nearby astrocytic cytoplasm (in either cell body or process) was measured.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As previous research has identified DM (and intermediate microglia, presenting features of both typical microglia and DM) as an abundant cell population in aging and neurodegenerative disease pathology (3,39,45,46), a quantitative approach to measuring the shade, or “darkness”, of microglia on electron micrographs was next employed. Using ImageJ, the integrated density of microglial cytoplasm and integrated density of nearby astrocytic cytoplasm (in either cell body or process) was measured.…”
Section: Methodsmentioning
confidence: 99%
“…for group-wise comparison. These ranges were chosen to match previous qualitative categorization of typical, intermediate, and dark microglia, respectively (3,39,45,46). In short, intermediate microglia can be distinguished from typical microglia based on their more electron-dense cytoplasm and heterochromatin pattern, accompanied by intermediate markers of cellular stress such as ER dilation (3,39,45,46).…”
Section: ‫݅ݐܴܽ‬ ൌ ‫݀݁ݐܽݎ݃݁ݐ݊ܫ‬ ‫ݕݐ݅ݏ݊݁݀‬ ‫ݏ‪݈݃݅ܽԣ‬ݎܿ݅݉‬ ‫݉ݏ݈ܽݐݕܿ‬ ‫݀݁...mentioning
confidence: 99%
See 1 more Smart Citation
“…Sections from two to four levels per animal (6-8 µm apart) were cut at a thickness of 73 nm and placed onto silicon wafers for SEM imaging using a Zeiss Crossbeam 350 SEM operating at a 1.4 kV voltage and 1.2 nA current. Images of the ultrathin sections were rst acquired at a resolution of 25 nm per pixel to allow for the identi cation of MG/MDM cell bodies with relation to the SCI site (25)(26)(27). MG/MDM located near the lesion area (directly contacting degraded myelinated axons or surrounded by parenchyma with clear signs of dystrophy or myelin alterations) and far (in proximity to the white matter of the dorsal column adjacent to the lesion surrounded by parenchyma without any signs of dystrophy or myelin alterations but observed in the same ultrathin section) were next imaged at a resolution of 5 nm per pixel for ultrastructural analyses.…”
Section: Tissue Post-xation For Scanning Electron Microscopymentioning
confidence: 99%
“…All images were blinded to the experimental conditions. We analyzed a total sample size of 79 MG/MDM cell bodies which was determined to be su cient to obtain statistical power based on the software G*Power V3.1 (effect size of 0.9; power of 0.9 estimated at 60 MG/MDM) (25,27,28). We did not perform immunostaining to distinguish MG/MDM as we wanted to further investigate the presence of glycogen granules within their cytoplasm (27) and the possible presence of dark MG (27,29).…”
Section: Tissue Post-xation For Scanning Electron Microscopymentioning
confidence: 99%